Blood pressure and left ventricular mass index in healthy adolescents. Issue 1 (February 2017) - Daimee, Usama A.; Lande, Marc B.; Tang, Wan; Tu, Xin M.; Veazie, Peter; Bisognano, John D.; Block, Robert; Teeters, John C.
Abstract : Primary hypertension among children and adolescents is increasing in prevalence and has been associated with the sequela of left ventricular hypertrophy (LVH), defined by increased left ventricular mass index (LVMI). The association between high blood pressure (BP) and LVMI in an otherwise healthy pediatric population is not well understood. We evaluated the relationship between measures of BP and LVMI in a group of healthy adolescents. We conducted a retrospective review of 55 high school athletes who participated in a community health screen, which included collecting BP readings and limited echocardiograms. End points included prevalence of BP in the ranges of hypertension and prehypertension, prevalence of LVH, and relationship between BP indices and LVMI. No individuals were found to be in the hypertensive range, and there were 13 (24%) in the prehypertensive range. Only one (2%) adolescent met LVH criteria. In multivariable regression analysis, increasing systolic BP index was the only variable significantly associated with greater LVMI ( P =0.028). In a healthy cohort of lean adolescents, BP in the prehypertensive range was common in the community health screen setting. Increasing systolic BP index was significantly associated with LVMI.